Surface Media: McLuhan, the Bauhaus and the Tactile Values of TV. (March 2022) - Schmidgen, Henning
Marshall McLuhan understood television (TV) as a tactile medium. This understanding implied what Bruno Latour might call a 'symmetrical' conception of tactility. According to McLuhan, not only human actors are endowed with the sense of touch. In addition, TV, digital computers and other 'electric media' use light beams and similar scanning techniques for ceaselessly 'caressing the contours' of their surroundings. This notion of tactility was crucially shaped by the holistic aesthetics of the early Bauhaus. To get at the specific features of the TV image, McLuhan relied on the writings of László Moholy-Nagy and Sigfried Giedion, in particular their use of photography for capturing and highlighting the 'texture' of surfaces. However, he hardly reflected the social and political factors that, in the age of electric media, contribute to the 'symmetricization' of touch.